WAJAH BAHASA LEMBAGA SWASTA DI KEPULAUAN RIAU: Kajian Lanskap Linguistik - Tasliati, Tasliati (Kementerian Sekretariat Negara Republik Indonesia, 2024)
This research is motivated by the linguistic conditions in private institutions in the Riau Islands, which signal a lack of adherence to the regulations prioritizing the national language in public spaces. Therefore, this study discusses the linguistic landscape of private institutions in the Riau Islands by utilizing linguistic landscape studies. The objective of this research is to describe the linguistic landscape of private institutions in the Riau Islands. Data for the research were collected using Simak (closely reading) methods with observation and documentation techniques. The data were then analyzed using agih (distribution) and padan (matching) methods. The research shows that in the linguistic landscape of private institutions in the Riau Archipelago, Indonesian does not occupy the primary or prestigious position. Its presence is overshadowed by foreign languages, particularly English. The dominance of English is found in all types of public space objects that are used as indicators of the linguistic landscape. The linguistic landscape of private institutions in the Riau Archipelago can be categorized as a permanently visible communication form. This means that the presentation of text and/or images in the public space of these institutions has been carefully planned, as evidenced by their permanent materials and strategic placement. Unfortunately, considerations regarding language rules or policies in Indonesia seem to have been overlooked.